A mediator model to predict workplace influenza vaccination behaviour: an application of the health action process approach - Ernsting, Anna; Gellert, Paul; Schneider, Michael; Lippke, Sonia (Psychology & health, 2013)
Purpose: Applying the health action process approach (HAPA) to vaccination behaviour as a single-event health behaviour to study vaccination adherence and its predictors in a worksite flu vaccination programme. Methods: A total of N = 823 employees participated in a longitudinal survey. Predictors (risk perception, self-efficacy, positive and negative outcome expectancies, intention and planning) were assessed at Time 1, and behaviour was assessed five months later at Time 2. Intention and planning were specified as mediators in a path analytical logistic regression model. Results: Risk perception, self-efficacy and positive as well as negative outcome expectancies predicted intention (R² = .76). Intention and planning predicted subsequent behaviour, and planning mediated the relation between intention and vaccination behaviour (R² = .67). In addition, results suggested the adjustment of the theoretical model: risk perception and negative outcome expectancies showed direct effects on behaviour resulting in a significantly better model fit. Conclusions: Findings support the general applicability of the HAPA to vaccination behaviour and the importance of planning for translating intentions into behaviour. However, the adjusted model was superior and underlined the particular role of risk perception and negative outcome expectancies for vaccination behaviour to explain underlying mechanisms in vaccination behaviour.